find the sum to n terms of the series , whose nth term is given by (2n - 1)*2
Answers
Answered by
1
Answer:
nth term=(2n-1) ×2
ist term =(2×1-1) ×2=2
second term=(4-1) ×2=6
3rd term=(6-1) ×2=10
so, series is given
2,6,10,.....(2n-1) ×2
this series is inA. P
d=10-6=6-2=4
istam term a=2
sum of nth term is =n/2[2a+(n-1) d]
Sn=n/2[2×2+(n-1) ×4]=n/2[4+4n-4]=n/2 *4n=2n²
Sn=2n².
Mark as Brainlist answer.
Similar questions
Accountancy,
6 months ago
History,
6 months ago
Physics,
6 months ago
Biology,
1 year ago
English,
1 year ago